2018
DOI: 10.5815/ijitcs.2018.08.07
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Descriptive Analysis of Breast Cancer Tissues Using K-means and SelfOrganizing Map

Abstract: Data mining is a descriptive and predictive data analytical technique that discovers meaningful and useful knowledge from dataset. Clustering is one of the descriptive analytic techniques of data mining that uses latent statistical information that exists among dataset to group them into meaningful and or useful groups. In clinical decision making, information from medical tests coupled with patients' medical history is used to make recommendations, and predictions. However, these voluminous medical datasets a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
0
0
Order By: Relevance
“…The aforementioned dataset includes highlights found from FNA test sweeps on a bosom growth. The informative index is divided into two parts for ML calculations: 70% for preparation and 30% for testing [13]. Their findings revealed that all of the ML computations introduced a better performance on the twofold order of carcinomas, such as determining whether growth is safe or harmful.…”
Section: Related Workmentioning
confidence: 99%
“…The aforementioned dataset includes highlights found from FNA test sweeps on a bosom growth. The informative index is divided into two parts for ML calculations: 70% for preparation and 30% for testing [13]. Their findings revealed that all of the ML computations introduced a better performance on the twofold order of carcinomas, such as determining whether growth is safe or harmful.…”
Section: Related Workmentioning
confidence: 99%